2006
DOI: 10.1103/physrevb.73.155201
|View full text |Cite
|
Sign up to set email alerts
|

Field- and concentration-tuned scaling of a quantum phase transition in a magnetically doped semiconductor

Abstract: Scaling analysis was performed on families of DC and AC conductivity curves falling on the metallic and insulating sides of the metal-insulator transition in the amorphous magnetically doped semiconductor, a-Gd x Si 1−x. The transport curves were obtained both as a function of discretely varying both the gadolinium dopant concentration, x, and separately by changing an applied magnetic field, H. Both tuning parameters result in correlation length exponents of = 1 and dynamical scaling exponents of z = 2. Tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Transport measurements in a-Gd x Si 1−x films revealed both insulating and metallic properties for x Ͻ 0.13 and x Ͼ 0.14, respectively. 19 We chose this material because its resistivity ͑ϳ2.5 m⍀ cm at low T͒ is high compared to more standard metallic spin glasses, which makes it more suitable for transport noise experiments.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Transport measurements in a-Gd x Si 1−x films revealed both insulating and metallic properties for x Ͻ 0.13 and x Ͼ 0.14, respectively. 19 We chose this material because its resistivity ͑ϳ2.5 m⍀ cm at low T͒ is high compared to more standard metallic spin glasses, which makes it more suitable for transport noise experiments.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…22 Similar magnetoconductance has in fact also been observed in amorphous metal semiconductor alloys, such as a-GdSi. 23 From the earliest reports the transport behavior of conducting polymer samples that fall on the insulating side of the MIT have been modeled using variable range hopping (VRH), 24 though the fits of the data over which this VRH occurs persist often to room temperature, which is quite different than insulating samples of metal semiconductor alloys which only exhibit VRH behavior up to approximately 20K and certainly much higher in temperature than doped crystalline semiconductor systems where VRH is observed up to even lower temperatures, depending on how far the sample is tuned into the insulating phase.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Gd-doped e-beam co-evaporated amorphous Si have shown strong interactions between the magnetic moments and carriers leading to very large negative MR (e.g. 10 5 at 1 K), anomalous magneto-optical properties and spin-glass freezing [ Refs 7,8,9,10]. The magnitude of this temperature-dependent negative MR below a characteristic temperature (T * ) was suggested to depend on electron screening related to the metallicity of the amorphous matrix [8].…”
Section: Introductionmentioning
confidence: 99%